Sexual and Gender Minority Health: What We Know and What Needs to Be Done - Mayer, Kenneth H. (American Public Health Association, 2008)
We describe the emergence of lesbian, gay, bisexual, and transgender (LGBT) health as a key area of study and practice for clinicians and public health professionals. We discuss the specific needs of LGBT populations on the basis of the most recent epidemiological and clinical investigations, methods for defining and measuring LGBT populations, and the barriers they face in obtaining appropriate care and services. We then discuss how clinicians and public health professionals can improve research methods, clinical outcomes, and service delivery for lesbian, gay, bisexual, and transgender people.